Ca(V)3.1 is a tremor rhythm pacemaker in the inferior olive - Park, Young-Gyun; Park, Hye-Yeon; Lee, C. Justin; Choi, Soonwook; Jo, Seonmi; Choi, Hansol; Kim, Yang-Hann; Shin, Hee-Sup; Llinas, Rodolfo R.; Kim, Daesoo (NATL ACAD SCIENCES, 2010)
The rhythmic motor pathway activation by pacemaker neurons or circuits in the brain has been proposed as the mechanism for the timing of motor coordination, and the abnormal potentiation of this mechanism may lead to a pathological tremor. Here, we show that the potentiation of Ca(V)3.1 T-type Ca2+ channels in the inferior olive contributes to the onset of the tremor in a pharmacological model of essential tremor. After administration of harmaline, 4- to 10-Hz synchronous neuronal activities arose from the IO and then propagated to cerebellar motor circuits in wild-type mice, but those rhythmic activities were absent in mice lacking Ca(V)3.1 gene. Intracellular recordings in brain-stem slices revealed that the Ca(V)3.1-deficient inferior olive neurons lacked the subthreshold oscillation of membrane potentials and failed to trigger 4- to 10-Hz rhythmic burst discharges in the presence of harmaline. In addition, the selective knockdown of Ca(V)3.1 gene in the inferior olive by shRNA efficiently suppressed the harmaline-induced tremor in wild-type mice. A mathematical model constructed based on data obtained from patch-clamping experiments indicated that harmaline could efficiently potentiate Ca(V)3.1 channels by changing voltage-dependent responsiveness in the hyperpolarizing direction. Thus, Ca(V)3.1 is a molecular pacemaker substrate for intrinsic neuronal oscillations of inferior olive neurons, and the potentiation of this mechanism can be considered as a pathological cause of essential tremor.
Keywords: BETA-CARBOLINES NORHARMAN; HARMALINE-INDUCED TREMOR; CALCIUM-CHANNELS; MICE LACKING; SYNCHRONIZED OSCILLATIONS; SUBTHRESHOLD OSCILLATIONS; CA2+ CHANNELS; I-H; NEURONS; CEREBELLAR